Making right choices : ethical leadership practices of public school heads - Baqued-qued, Gay C. (Saint Louis College, City of San Fernando, La Union : [s.n.], 2021)
This study aimed to determine and analyze the extent of ethical leadership practices of school heads in the City Schools Division of San Fernando as a basis for ethical leadership training program. The study utilized the sequential explanatory descriptive research design by Plano (2011) where the quantitative phase is followed by the qualitative phase. Data were obtained through a validated two-part questionnaire followed by interviewing school heads. Total enumeration of the 40 school heads from City Schools Division of San Fernando and 40 master teachers were the respondents for the quantitative data. Fishbowl sampling was used for the interview of seven (7) school heads. The extent of ethical leadership practices was always practiced. There was a significant difference in the extent of ethical leadership practices as perceived by the respondents. There was a significant relationship of the seminars and trainings on ethics and morality and extent of ethical leadership practices. The qualitative data focused on the moral and ethical issues encountered by the school heads and the ways on how they address moral and ethical issues encountered. The least among ethical leadership practices and the moral and ethical issues encountered were the basis of the Ethical Leadership Training Program
References: pages 137-152.
CHED-La Union
Keywords: Schools administration